Satisfaction of Long Distance Marriage Couple - Afdal Afdal; Vany Enika Mailinda; Wike Safitri; Denia Syapitri (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2022)
Long-distance marriage is when marriage couple living separately for various reasons and one of them is work. Tipically, affecting couple's complaint of marital dissatisfaction. This study uses a qualitative and descriptive approach to analyze marital satisfaction of long-distance marriage couples. The subjects were 4 housewife selected using a purposive sampling technique based on specific aspects (characteristics), specifically a couple who are having a long-distance marriage for approximately 1 year. Data were collected through observation and semi-structured interviews. Furthermore, the data were analyzed through four stages of data collection, reduction, presentation, and conclusion drawing. The results showed that subjects 1, 2, and 3 felt satisfied in a marriage relationship except subject 4, who was dissatisfied. There were no difficulties in the four subjects' relationships with their partners because they were able to communicate effectively. Moreover, all of them could solve problems and cope well with the household economic situation. This study imply that the involvement of a counselor is essential in providing subjects with a variety of approaches. The therapeutic communication between counselors and subjects, in particular LDM couples, can be used to provide services to others.